Evaluation of the Jaklitera Application’s User Experience Using the User Experience Questionnaire (UEQ) - Yopi Handrianto; Alif Septiandi (LPPM Universitas Bina Sarana Informatika, 2026)
The Jaklitera application, developed by the Jakarta Library and the HB Jassin Literary Documentation Center, serves as an innovation aimed at expanding public access to digital literacy. This study aims to evaluate the quality of user experience of the application and analyze the influence of pragmatic quality and hedonic quality on attractiveness as a representation of overall user perception. This research adopts a quantitative approach using the User Experience Questionnaire (UEQ), which consists of six dimensions. Data were collected from 100 Jaklitera users using purposive sampling. Multiple linear regression was employed to analyze the relationships among variables. The results indicate that the Jaklitera application provides a very positive user experience. Pragmatic quality and hedonic quality significantly influence attractiveness, accounting for 86.3% of the variance, while the remaining 13.7% is influenced by other factors. These findings highlight that both functional and enjoyable user experiences play a crucial role in increasing application attractiveness.